Family Medicine in Guantánamo: history, achievements and challenges - María Inés Jiménez de Castro Morgado; Yuleisi de la Cruz Carmenaty; Ana Margarita Sánchez Figueredo (Revista Información Científica)
Editorial article that addresses the history, achievements and challenges of the Family Medicine specialty in the province of Guantánamo, in memory of its 40th anniversary, started in the southern area of the city on November 14, 1984.